Correlation of the Interlukein-8 with Breast Cancer Patients in Iraqi Woman’s (Journal of Pharmaceutical Negative Results, 2022)
Almost one-third of all female malignancies recorded in Iraq's most recent Iraqi Cancer Registry are breast cancers, making it the most common kind among women. With an anticipated 9.6 million deaths due to cancer in 2018, it is the second largest cause of death worldwide. One out of every six people who die in the world does so as a result of cancer. In low- and middle-income nations, cancer kills more than 70 percent of the population. Methods: This study include 49 samples patients and 40 samples (control group) which collection by draw of blood by gel tube and also the specimens were used centrifuge to get serum to measuring the interlukein-8 level by ELISA technique to both groups (patients, control). Results: measured IL-8 levels by ELISA technique and the results were referred to raise in IL-8 levels of BC females for serum samples compared with control group (healthy women). The cutoff value of serum IL-8 was >26.73 with good sensitivity, specificity and accuracy level respectively (73.47 %, 75 % and 72.0 %). The serum level of IL-8 was significantly higher in breast cancer group in comparison with control group, 36.69 (27.39) fold change versus 20.55 (13.83) fold change, respectively (p < 0.001). Conclusion: This study has found that the investigated interlukein-8 levels were associated with moderate to high grade carcinoma, this study may clarify that IL-8 along very important predictive and diagnostic marker for breast cancer and treatment responsiveness.